2013
DOI: 10.1021/am402456s
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Sensitive and Selective NO Probe Based on Villi-like WO3 Nanostructures for Application to Exhaled Breath Analyzers

Abstract: Self-assembled WO3 thin film nanostructures with 1-dimensional villi-like nanofingers (VLNF) have been synthesized on the SiO2/Si substrate with Pt interdigitated electrodes using glancing angle deposition (GAD). Room-temperature deposition of WO3 by GAD resulted in anisotropic nanostructures with large aspect ratio and porosity having a relative surface area, which is about 32 times larger than that of a plain WO3 film. A WO3 VLNF sensor shows extremely high response to nitric oxide (NO) at 200 °C in 80% of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 53 publications
0
57
0
1
Order By: Relevance
“…and methane at mild temperatures (150°C) [470]. Similarly, tungsten oxide (WO 3 ) nanocolumns have been used as conductometric sensors of NO, NO 2 and ethanol [471][472][473]. To illustrate the possibilities and lay-out of a typical OAD conductimetry sensor device, Fig.…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…and methane at mild temperatures (150°C) [470]. Similarly, tungsten oxide (WO 3 ) nanocolumns have been used as conductometric sensors of NO, NO 2 and ethanol [471][472][473]. To illustrate the possibilities and lay-out of a typical OAD conductimetry sensor device, Fig.…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
“…To illustrate the possibilities and lay-out of a typical OAD conductimetry sensor device, Fig. 5.10 summarizes some of the results obtained with one of these WO 3 sensors [471] in the detection of NO. This particular system consists of MS-OAD WO 3 films grown on interdigitated Pt electrodes.…”
Section: Gas and Vapor Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its high response, WO 3 , an ntype semiconductor with a bandgap of 2.8 eV, is one of the most promising materials for the sensing of NO x gases. Moon et al [9] synthesized one-dimensional villi-like nano-fingers of WO 3 on SiO 2 /Si substrate with Pt interdigitated electrodes, and found that the sensor showed high response to NO at 200 °C. Chen et al [10] improved the low-temperature response and selectivity of WO 3 -based sensors by modifying the WO 3 nano-plates with Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is easy to synthesize as various nanostructures, but as a sensor its selectivity is poor. Among these n-type semiconductors, WO 3 has the best sensitivity to NO, but a long recovery time inhibits the application of WO 3 in many cases [2,[16][17][18][19] other elements and forming composite with other materials are the strategies commonly used [20][21][22][23][24][25]. It is generally agreed that the noble metal decoration enhances both the sensitivity and responding speed [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%